SNP rs4937333 in the miRNA-5003-Binding Site of the ETS1 3′-UTR Decreases ETS1 Expression - Zhang, Ruixian; Pan, Bangpin; Li, Yi; Li, Xiaolan (Frontiers in Genetics, 2019)
The ETS1 gene is mutated and reduced-expressed in systemic lupus erythematosus (SLE). Here, we investigate the association of ETS1 polymorphism in the 3’ untranslated regions (3’UTRs) with SLE and its regulation on ETS1 expression in Chinese population. We found that the rs4937333 T allele was associated with a significantly increased risk of SLE (OR = 1.800, 95% CI, 1.02–3.157, p = 0.040), and with dramatically reduced levels of ETS1 in B cells from SLE. Functionally, the rs4937333 T allele altered the binding affinity between miR-5003 and its ETS1 3′UTR target, thus enhancing the suppression of ETS1 expression. Furtherly, IgM-secreting plasmocytes were reduced significantly in B cells with rs4937333 C allele than in T ones using FACS and ELISA. Additionally, miR-5003 was higher-expressed in B cells than in T cells of SLE patients, and the positive correlation between miR-5003 and ETS1 was found, especially in B cells with T allele. These findings suggest rs4937333 T allele was a risk factor for the susceptibility of SLE in Chinese population. It could enhance the activity of miR-5003 binding to ETS1, which probably regulates ETS1 to involve in differentiation of B cells into plasmacytes.